(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
Pachira glabra is one of the abundant underutilized plants in the tropics. The seeds were processed into flour. A sample of the flour were evaluated for physicochemical composition, functional properties, baking test and the bread produced were subjected to sensory analysis. The results of proximate analysis showed that P. glabra flour had significantly higher total fat content, Crude fiber and total ash content (P>0.05), but with lower values of other components when compared with the white wheat flour. The anti – nutrient properties of P. glabra flour such as; Tannins, Phytates, Oxalates and Alkaloids were obtained to be; 3.29, 6.99, 3.74 and 1.98 mg/100g respectively. The functional properties of P. glabra flour had significantly higher in WAC, and swelling capacity (P>0.05), but with lower values of forming capacity and OAC, both the two samples had the same value of bulk density. P. glabra flour may find its use in food industry. The volume of the bread obtained after baking test showed a decrease of bread volume with an increase in P. glabra flour substitution. The results of Sensory evaluation gotten from the panelist were statistically analyzed using ANOVA and there was significant difference in colour, aroma and overall acceptability but no significant difference in taste, and texture.